PENYULUHAN MEDIA BANNER BERBASIS SEJARAH LOKAL RUMAH KAMPUNG ARAB PALEMBANG UNTUK MENINGKATKAN MINAT DAN MOTIVASI BELAJAR SISWA - Setyawati, Dewi; Apriana, Apriana; Yuliarni, Yuliarni; Heryati, Heryati; Ramadhan, Nur; Octavian, Wendy Anugrah (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2024)
This service activity was motivated by the low interest of history teachers in creating media, especially in history subjects. Apart from that, there is also low student interest and motivation in learning, especially local history. So far, teachers in carrying out learning tend not to use media as a tool in conveying learning material, so learning is verbalistic plus the perception of history for some students is still considered a relatively difficult lesson. Therefore, it is necessary to create learning conditions that can familiarize children with history and their environment, one of which is by conducting learning using Banner media. This service activity aims to educate Palembang City YWKA High School teachers to increase their professionalism as History Teachers at Palembang YWKA High School. This activity also motivates teachers to design attractive learning media in the form of banners using local sources of excellence in the city of Palembang. The method of implementing activities carried out in this activity is lecture, question and answer and discussion, and the practice of making Banner media. It can be concluded that educational activities for YWKA High School Teachers in Palembang City provide teachers with understanding and skills in producing Banner learning media based on the local history of Arab Village Houses in Palembang City.